2011
DOI: 10.1016/j.ydbio.2010.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between oligodendrocyte precursors control the onset of CNS myelination

Abstract: The formation of CNS myelin is dependent on the differentiation of oligodendrocyte precursor cells (OPCs) and oligodendrocyte maturation. How the initiation of myelination is regulated is unclear but it is likely to depend on the development of competence by oligodendrocytes and receptivity by target axons. Here we identify an additional level of control of oligodendrocyte maturation mediated by interactions between the different cellular components of the oligodendrocyte lineage. During development oligodendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 55 publications
1
32
0
2
Order By: Relevance
“…Here, we depict a dose-and time-dependent irregularity in the expression levels of MBP, the recognized major myelin indicator (Yang et al, 2011). The anomalous levels of PLP and CNPase, enriched in compacted (Schneider et al, 1995) and un-compacted myelin (Baumann and Pham-Dinh, 2001) respectively, denote a degeneration in the myelin multi-lamellar structure as well as myelin forming oligodendrocytes in cerebral cortex.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Here, we depict a dose-and time-dependent irregularity in the expression levels of MBP, the recognized major myelin indicator (Yang et al, 2011). The anomalous levels of PLP and CNPase, enriched in compacted (Schneider et al, 1995) and un-compacted myelin (Baumann and Pham-Dinh, 2001) respectively, denote a degeneration in the myelin multi-lamellar structure as well as myelin forming oligodendrocytes in cerebral cortex.…”
Section: Discussionmentioning
confidence: 97%
“…The structural integrity of myelin sheath in brain is dependent on the maturation of oligodendrocytes and axon (Yang et al, 2011), marked majorly by the myelin basic protein (MBP) and neurofilament (NF) respectively (Pons-Vazquez et al, 2011). The proteolipid protein (PLP) is vital for generating the multilayered structure of myelin Toxicology and Applied Pharmacology xxx (2013) xxx-xxx (Fulton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the final number of mature oligodendrocytes will remain the same even when the number of OPCs increases (Yang et al, 2011). This behavior may be the result of several different regulatory mechanisms in the brain, including apoptotic pathways triggered by a high OPC density, the inhibition of OPC proliferation when a critical number of cells has been reached or even competition between early and late OPCs that results in the survival of one group over the other (Yang et al, 2011). These potential mechanisms suggest that changes in OPC proliferation may not be observable even when other changes are observed in this mouse model.…”
Section: Discussionmentioning
confidence: 98%
“…However, there do appear to be changes in the OPC maturation rate, based on the earlier increase of MBP (characteristic of mature OLs) in day 10 TG mice. Previous studies have shown that the final number of mature oligodendrocytes will remain the same even when the number of OPCs increases (Yang et al, 2011). This behavior may be the result of several different regulatory mechanisms in the brain, including apoptotic pathways triggered by a high OPC density, the inhibition of OPC proliferation when a critical number of cells has been reached or even competition between early and late OPCs that results in the survival of one group over the other (Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…To be considered in this review is the capacity of current therapeutic agents to promote these functions or protect the cells from putative immune-mediated injury. Remyelination is considered to be dependent on recruitment and differentiation of OPCs [12].…”
Section: Ols/opcsmentioning
confidence: 99%